High performance faster-than-nyquist signaling - Cunha, Bruno Miguel Domingues da (2015)
AbstractIn a wireless broadband context, multi-path dispersive channels can severely affectdata communication of Mobile Terminals (MTs) uplink.Single Carrier withFrequency-Domain Equalization (SC-FDE) has been proposed to deal with highlydispersive channels for the uplink of broadband wireless systems. However, currentsystems rely on older assumptions of the Nyquist theorem and assume that a systemneeds a minimum bandwidth 2Wper MT. Faster-Than-Nyquist (FTN) assumesthat it is possible to employ a bandwidth as low as 0.802 of the original Nyquistbandwidth with minimum loss - despite this, the current literature has only proposedcomplex receivers for a simple characterization of the wireless channel. Furthermore,the uplink of SC-FDE can be severely affected by a deep-fade and or poor channelconditions; to cope with such difficulties Diversity Combining (DC) Hybrid ARQ(H-ARQ) is a viable technique, since it combines the several packet copies sent bya MT to create reliable packet symbols at the receiver.In this thesis we consider the use of FTN signaling for the uplink of broadbandwireless systems employing SC-FDE based on the Iterative Block with DecisionFeedback Equalization (IB-DFE) receiver with a simple scheduled access HybridAutomatic Repeat reQuest (H-ARQ) specially designed taking into account thecharacteristics of FTN signals. This approach achieves a better performance thanNyquist signaling by taking advantage of the additional bandwidth employed of aroot-raised cosine pulse for additional diversity.Alongside a Packet Error Rate (PER) analytical model, simulation results show that this receiver presents a better performance when compared with a regular system,with higher system throughputs and a lower Energy per Useful Packet (EPUP).